Low genetic differentiation between apotheciate Usnea florida and sorediate Usnea subfloridana (Parmeliaceae, Ascomycota) based on microsatellite data. Issue 10 (October 2020) - Degtjarenko, Polina; Mark, Kristiina; Moisejevs, Rolands; Himelbrant, Dmitry; Stepanchikova, Irina; Tsurykau, Andrei; Randlane, Tiina; Scheidegger, Christoph
Abstract: Accurate species delimitation has a pivotal role in conservation biology, and it is especially important for threatened species where decisions have political and economic consequences. Finding and applying appropriate character sets and analytical tools to resolve interspecific relationships remains challenging in lichenized fungi. The main aim of our study was to re-assess the species boundaries between  Usnea subfloridana  and  Usnea florida, which have been phylogenetically indistinguishable until now, but are different in reproductive mode and ecological preferences, using fungal-specific simple sequence repeats (SSR), i.e. microsatellite markers. Bayesian clustering analysis, discriminant analysis of principal components (DAPC), minimal spanning network (MSN), and principal component analysis (PCA) failed to separate  U. florida  and  U. subfloridana  populations. However, a low significant differentiation between the two taxa was observed across all populations according to AMOVA results. Also, analysis of shared haplotypes and statistical difference in clonal diversity (M) supported the present-day isolation between the apotheciate  U. florida  and predominantly sorediate  U. subfloridana . Our results do not provide a clear support either for the separation of species in this pair or the synonymization of  U. florida  and  U. subfloridana . We suggest that genome-wide data could help resolve the taxonomic question in this species pair. Highlights: Species boundaries between Usnea florida and Usnea subfloridana were re-assessed. Microsatellite markers were used for species delimitation purposes. A high level of gene flow must have occurred between Usnea populations. Our study does not support either for separation or synonymization of study taxa.